2017
DOI: 10.1080/02640414.2017.1348614
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical differences of arm swing countermovement jumps on sand and rigid surface performed by elite beach volleyball players

Abstract: The purpose of this study was to investigate the possible arm swing effect on the biomechanical parameters of vertical counter movement jump due to differences of the compliance of the take-off surface. Fifteen elite male beach-volleyball players (26.2 ± 5.9 years; 1.87 ± 0.05 m; 83.4 ± 6.0 kg; mean ± standard deviation, respectively) performed counter movement jumps on sand and on a rigid surface with and without an arm swing. Results showed significant (p < .05) surface effects on the jump height, the ankle … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
64
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(74 citation statements)
references
References 40 publications
7
64
1
2
Order By: Relevance
“…Our results suggest that jumping coordination remains similar between surfaces. This robust pattern of coordination between the main lower limb joints during jumping is also present when CMJ are performed on stiffer, steel-made force plate or soft and highly deformable sand surface ( Giatsis et al, 2018 ). Similar joint range of motion (i.e., flexion and extension) and time to perform the preparatory countermovement and push-off were found between surfaces, which indicate that participants kept the same jumping strategy whatsoever the type of surface.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…Our results suggest that jumping coordination remains similar between surfaces. This robust pattern of coordination between the main lower limb joints during jumping is also present when CMJ are performed on stiffer, steel-made force plate or soft and highly deformable sand surface ( Giatsis et al, 2018 ). Similar joint range of motion (i.e., flexion and extension) and time to perform the preparatory countermovement and push-off were found between surfaces, which indicate that participants kept the same jumping strategy whatsoever the type of surface.…”
Section: Discussionmentioning
confidence: 88%
“…However, we observed an increase in peak ankle plantar flexion velocity (i.e., reached ∼35 ms before toe-off) on the hybrid turf (+7 ± 9%; significant) and artificial turf (+6 ± 8%; non-significant) compared to the athletic track ( Table 1 ). This higher ankle angular velocity could be possible because of smaller resistance at ankle plantar flexion on the more deformable surfaces ( Giatsis et al, 2018 ). Previously, Giatsis et al (2018) showed that a decreased resistance due to an increase in surface compliance resulted in both a larger ankle range of motion and angular velocity during CMJ on sand compared to a stiff surface.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The release time of the stored elastic energy can be optimized by increasing the amount of activity of the eccentric muscle (McBride, McCaulley, & Cormie, 2008;Finni, Komi, & Lepola, 2000). These results are based on the fact that maximal vertical jumps need a greater engagement of the hip extensor muscles (Giatsis, Panoutsakopoulos, & Kollias, 2018;Bobbert & Casius, 2005;Lees, Vanrenterghem, & De Clercq, 2004) and we saw that volleyball players have the best result in jump height (H).…”
Section: Discussionmentioning
confidence: 88%
“…Imediatamente a perna de elevação dá um passo e chega ao lado da perna de impulsão para iniciar a elevação do centro de gravidade do solo e o tornozelo realiza uma veloz flexão plantar com extensão das demais articulações (joelho, quadril e coluna vertebral) para continuar a alta velocidade vertical que vai propiciar uma ótima impulsão (Shalmanov, 1998). No voleibol na areia difere ao da quadra, ocorre mínima flexão plantar e dessa maneira essa ação se acentua até o jogador perder o contato com a areia fofa, sendo realizado com rapidez para gerar uma alta velocidade vertical e ocasionar uma ótima impulsão (Giatsis, Panoutsakopoulos & Kollias, 2018).…”
Section: Figura 3 Velocidade Horizontal Da Corrida De Aproximação Dounclassified